Monetary policy spillover to small open economies: Is the transmission different under low interest rates? - Jin Cao; Valeriya Dinger; Tomás Gómez; Zuzana Grice; Martin Hodula; Alejandro Jara R.; Ragnar Enger Juelsrud; Karolis Liaudinskas; Simona Malovaná; Yaz Terajima (Norges Bank, 2021)
We explore the impact of low and negative monetary policy rates in core world economies on bank lending in four small open economies - Canada, Chile, the Czech Republic and Norway - using confidential bank-level data. Our results show that the impact on lending in these small open economies depends on the interest rate level in the core. When interest rates are high, monetary policy cuts in core economies can reduce credit supply in small open economies. In contrast, when interest rates in core economies are low, further expansionary monetary policy increases lending in small open economies, consistent with an international bank lending channel. These results have important policy implications, suggesting that central banks in small open economies should watch for the impact of potential regime switches in core economies' monetary policy when rates shift to and from the very low end of the distribution.
hdl:11250/2829106
Keywords: E43; E52; E58; F34; F42; G21; G28; 330; Low and negative interest rate environment (LNIRE); Cross-border monetary policy spillover; International bank lending channel; Portfolio channel